Mapping the Literature on the Relationship between Indonesia and Chile as Non-Traditional Partners - Rachmasari Nur Al-Husin; Asra Virgianita (Journal La Sociale, 2024)
Indonesia and Chile formed a comprehensive trade cooperation called the Indonesia-Chile Comprehensive Economic Partnership Agreement (IC-CEPA). Empirically, the relationship between Indonesia and Chile is not strong, so it is interesting to see how are the dynamics of the relationship between the two countries which are non-traditional partners but established comprehensive trade cooperation. Therefore, this literature review found 25 literatures that have discussed the dynamics of the relationship between Indonesia and Chile. This literature review maps the literature using the taxonomy method into three main topics, namely (1) the historical relationship between Indonesia and Chile, (2) the political relationship between Indonesia and Chile, (3) the economic relationship between Indonesia and Chile. This literature review found that the relationship between Indonesia and Chile in various fields shows a fluctuating trend because they still focus on traditional partners, the relationship between the two countries is pragmatic, lack of political will, and lack of information about each other's characteristics.